Modelfor Financing Agro Projects in Islamic Banking Institutions - Muhammad Ridhwan Ab. Aziz; Muhammad Mohamad Yusof (International Association of Islamic Banks (IAIB), 2024)
Journal of Islamic Banking & Finance . Jul-Sep2019, Vol. 36 Issue 3, p39-49. 11p.